PENYUSUNAN LAPORAN KEUANGAN SEDERHANA SEBAGAI PENDUKUNG SYARAT KREDIT PADA UMKM DI KOTA YOGYAKARTA: PREPARATION OF SIMPLE FINANCIAL REPORTS TO SUPPORT CREDIT REQUIREMENTS FOR MSMEs IN THE CITY OF YOGYAKARTA - Dea Rinda Anggreini; Rochmad Bayu Utomo (Pakis Journal Institute, 2023)
Financial statements are very important in a business because they record income and expenses, as well as the amount of profit earned. Financial reports are a tool for strategizing, decision-making, and complementary documents in applying for credit. From the results of interviews with business actors Warung Makan Barokah and Angkringan Tepi Barat, there is a lack of understanding and the importance of making simple financial reports in running a business. The purpose of this community service is to provide education, training, and assistance in preparing simple financial reports for MSME actors. The methods used in this service are 1) Survey, 2) Submission of Material, 3) Training and Mentoring, 4) Evaluation. The results of this community service are, that there are still many MSME players who do not record financial reports. Therefore, community service is carried out regarding assistance in preparing simple financial reports so that business actors can know the amount of profit every day.